2012
DOI: 10.7196/samj.5763
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physiological concentrations of bile acids on in vitro growth of Mycobacterium tuberculosis

Abstract: Intestinal tuberculosis (ITB) involves the ileocaecum in the majority of cases with upper gastrointestinal tract tuberculosis accounting for less than 3% of all cases.1 Gallbladder TB, in particular, is very rare, with few cases reported in the literature. ITB results from haematogenous spread or spread from contiguous lymph nodes or swallowed infected sputum.2 Why ITB preferentially affects the ileocaecum is unclear, but proposed mechanisms include bowel stasis in the terminal ileum, due to the ileocaecal val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…However, the abundances of OTU1842 ( Rhodoccus ), OTU2051 ( Enterococcus ), OTU233 ( Lactobacillus ), OTU1836 ( Lactobacillus ), OTU1837 ( Streptococcus ), and OTU176 ( Acinetobacter ) were significantly downregulated in the HCS group ( P < 0.05, Figure G). Of note, the above bacterial species have been reported to be closely related to the bile acid metabolism. We further measured the activity of BSH in the intestinal contents, which was secreted by intestinal bacteria to catalyze bile acids. The result showed that BSH activity was significantly downregulated in the intestinal contents of fish fed with a high-carbohydrate diet, whereas it was significantly upregulated in the intestinal contents of fish fed with a high-carbohydrate diet supplemented with B.…”
Section: Resultsmentioning
confidence: 99%
“…However, the abundances of OTU1842 ( Rhodoccus ), OTU2051 ( Enterococcus ), OTU233 ( Lactobacillus ), OTU1836 ( Lactobacillus ), OTU1837 ( Streptococcus ), and OTU176 ( Acinetobacter ) were significantly downregulated in the HCS group ( P < 0.05, Figure G). Of note, the above bacterial species have been reported to be closely related to the bile acid metabolism. We further measured the activity of BSH in the intestinal contents, which was secreted by intestinal bacteria to catalyze bile acids. The result showed that BSH activity was significantly downregulated in the intestinal contents of fish fed with a high-carbohydrate diet, whereas it was significantly upregulated in the intestinal contents of fish fed with a high-carbohydrate diet supplemented with B.…”
Section: Resultsmentioning
confidence: 99%
“…3 Cholelithiasis, cystic duct obstruction with an alteration in the composition of bileis important for the development of GBTB. In 70% of GBTB, cholelithiasis is present and it is common in females.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways may also be involved in host defense. Indeed, some bile acids inhibit the in vitro growth of M. tuberculosis [27]. Bile acid derivatives are also potential anti-TB agents [28], and purine metabolism in M. tuberculosis is a target for drug development [29,30].…”
Section: Plos Onementioning
confidence: 99%